LOS CONSORCIOS DE EXPORTACIÓN: REVISIÓN CONCEPTUAL Y FACTORES DETERMINANTES DE ÉXITO - Álvaro Espejo León; Fernando Fuentes García; Julia Núñez Tabales (Revista de Estudios Empresariales. Segunda Época, 2015)
Associationism is composed by different ways of cooperation between companies. It can be reflected because of a variety of concepts which are not similar between them. Sometimes, those concepts are differentiated by slight nuances and sometimes, they do not. Paying attention to the concept and to the dissimilar ways of companies’ association is indispensable not to address to export consortium as a formula. The work presented here aims to make a review of the existing literature , both theoretical and case study that serves as a compilation for further empirical research. At work the following main findings contributions or wanted: provide an evolutionary interpretation of the concept of export consortium , gathering the main factors that lead the company to go abroad under this formula , analyze what is published on the survival in the time of export consortia , shed light on the different types of export consortia exist and a compilation of the major determinants of success or failure of this form of association.